2021
DOI: 10.1016/j.neuroimage.2021.118639
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium metabolic imaging in the human brain at 9.4 Tesla with high spatial and temporal resolution

Abstract: Purpose To present first highly spatially resolved deuterium metabolic imaging (DMI) measurements of the human brain acquired with a dedicated coil design and a fast chemical shift imaging (CSI) sequence at an ultrahigh field strength of B 0 = 9.4 T. 2 H metabolic measurements with a temporal resolution of 10 min enabled the investigation of the glucose metabolism in healthy human subjects. Methods The study was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
73
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 39 publications
(66 reference statements)
7
73
2
Order By: Relevance
“…This work could not separate 2 H-lactate from 2 H-lipids, although the 1.35 ppm peak increased by 93% in the first experiment, suggesting that about half the measured peak is likely from the formation of lactate. This contrasts with a recent study in humans at 9.4 T (Ruhm et al, 2021), which found the lipid signal exceeded lactate, which may be the result of using a surface array coil for reception. In comparison with the birdcage coil used here, surface arrays greatly amplify signal from scalp lipids.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This work could not separate 2 H-lactate from 2 H-lipids, although the 1.35 ppm peak increased by 93% in the first experiment, suggesting that about half the measured peak is likely from the formation of lactate. This contrasts with a recent study in humans at 9.4 T (Ruhm et al, 2021), which found the lipid signal exceeded lactate, which may be the result of using a surface array coil for reception. In comparison with the birdcage coil used here, surface arrays greatly amplify signal from scalp lipids.…”
Section: Discussioncontrasting
confidence: 99%
“…One of the major challenges in undertaking a direct comparison between the two techniques in humans is that 13 C-HPMRI is usually undertaken at 3 T, which allows good spectral separation of metabolites while maintaining a sufficiently long relaxation time for the hyperpolarized signal to enable detection of both the injected hyperpolarized substrate and the subsequently formed metabolites (Vaeggemose et al, 2021). In comparison, DMI has been applied at field strengths of up to 16.4 T for improved spectral separation and signal-to-noise (Lu et al, 2017), with clinical DMI having previously been undertaken at field strengths of 4 T and higher, which are not used in routine clinical practice (De Feyter et al, 2018; de Graaf et al, 2020; Ruhm et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since its development, DMI has been used to evaluate glucose metabolism in healthy animal 9 and human 8 brain, to characterize glioblastoma brain tumors (GBM) in humans 8 and animals 10 via the Warburg effect, and to assess brown adipose tissue 11 as well as myocardial tissue 12 . Most recently, the performance of DMI has been demonstrated at 9.4T, 13 substantiating the previous sensitivity prediction 14 . In addition to its promising performance and extensive applications, DMI is robust and simple to perform, suggesting a high potential to be transformed into a clinical metabolic imaging method.…”
Section: Introductionmentioning
confidence: 99%